The effect of contact time between alginate impression material and type III dental stone on the surface properties of stone casts - Dulaimi, Suha F; Alnaser, Atyaf M; Hameed, Najwah Y (Journal of Baghdad College of Dentistry, 2021)
Background: Alginate impression material is the irreversible hydrocolloid material that is widely used in dentistry. The contact time between alginate and gypsum cast could have a detrimental effect on the properties of the gypsum cast. The objective of this study is to evaluate the impact of various contact time intervals of Alginate impressions & type III dental stone on surface properties of stone cast. Materials and Methods: Time intervals tested were 1hour, 6 hours and 9 hours. Surface properties of stone cast evaluated were surface detail reproduction, hardness and roughness. Surface detail reproduction was determined using cylindrical brass test block in accordance with ISO 1563. Surface roughness was measured by profilometer and hardness was measured by Durometer (Shore D). Results: The detail reproduction showed significant difference (P